Universal algebra : fundamentals and selected topics - Bergman, C. H. (Pure and applied mathematics, 2012)
"Preface This text is based on the two-semester course that I have taught over the years at Iowa State University. In the writing, as in my course, I attempt to convey my enthusiasm for the subject and my feelings that it is a worthy object of study for both graduate students and professional mathematicians. In choosing the level of detail, I have taken my inspiration more from the tradition of first-year algebra texts such as van der Waerden, Lang, and Dummit and Foote, than from a typical research monograph. The book is addressed to newcomers to the field, whom I do not wish to overwhelm, more than to veterans seeking an encyclopedic reference work. It is the job of the author to decide what to omit. One rule of thumb that I have always used in my classes is to introduce a tool only if it will be applied later in the course. As a teacher, I have always found it frustrating to expend a lot of effort and class time developing some construction and then not be able to demonstrate its importance. Thus, for example, in Chapter 7, the basics of commutator theory are developed in the context of congruence-permutable varieties and applied to the characterization of directly representable varieties. The more involved development in the congruence-modular case is omitted since it isn't needed for this application. As I have matured as a teacher, I have come to incorporate many more examples into all of my classes. I have applied that philosophy to the writing of this book. Throughout the text a series of examples is developed that can be used repeatedly to illustrate new concepts as they are introduced"--